Investigation of small ruminant lentivirus infections by serological and molecular methods in eastern mediterranean region - Fırat Doğan; Veysel Soydal Ataseven; Seval Bilge Dağalp; Yaşar Ergün (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the presence of small ruminant lentivirus infections in samples taken from goat and sheep farms. Materials and Methods: In this study, leukocyte and blood serum samples were taken from a total of 700 animals, including 260 sheep and 440 goats aged 6 months and over, from public-owned goats and sheep farms collected from the Eastern Mediterranean region (Hatay, Kahramanmaraş and Osmaniye) between 2015-2017 year. Serologic (ELISA) and molecular method (PCR) tests were used to reveal the presence of small ruminant lentivirus. Results: According to the results of ELISA and / or PCR tests, positivity was detected at a rate of 9.62% (25/260) in sheep, 9.32% (41/440) in goats and 9.43% (66/700) in all animals. In addition, as a result of the partial sequence analysis of the gag gene region, the presence of the B genotype of small ruminant lentivirus was detected in both sheep and goats. Conclusion: As a result, the situation of small ruminant lentiviruses in the Eastern Mediterranean (Hatay, Kahramanmaraş, Osmaniye) region in the recent past has been revealed. In this study, it was concluded that ELISA and PCR tests should be used together for the diagnosis of small ruminant lentivirus infections and complete herd-based eradication. In addition, it may be important to increase molecular studies, to reveal different subtypes by conducting detailed researches on different gene regions and full genome analysis, thus determining the subtypes circulating in the country.